2023
DOI: 10.1080/19490976.2023.2278225
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiome in healthy aging versus those associated with frailty

Mi Young Lim,
Young-Do Nam

Abstract: As the proportion of older people in the world’s population steadily increases, there is an urgent need to identify ways to support healthy aging. The gut microbiome has been proposed to be involved in aging-related diseases and has become an attractive target for improving health in older people. Herein, we cover the relationship between the gut microbiome and chronological age in adults, and then, we discuss the gut microbiome features associated with frailty, as a hallmark of unhealthy aging in older people… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 97 publications
0
9
0
Order By: Relevance
“…Furthermore, numerous studies have suggested that bacteriotherapy using three slightly different agents: probiotics, prebiotics, and synbiotics are promising for the prevention and treatment of human general aging and age-related disorders, 5 , 103 , 157–161 in which Lactobacillus and bifidobacterium are the most commonly used, though the effects varied across studies, which depending on dosage, duration, and their components. 162 Several clinical trials have demonstrated that the intake of a probiotic mixture decreasing inflammatory levels, increased the abundance of an anti-inflammatory commensal bacterium and improved cognitive function in older people. 80 , 131 Additionally, studies have shown that some probiotic strains have beneficial effects on male reproductive dysfunction.…”
Section: Perspectivesmentioning
confidence: 99%
“…Furthermore, numerous studies have suggested that bacteriotherapy using three slightly different agents: probiotics, prebiotics, and synbiotics are promising for the prevention and treatment of human general aging and age-related disorders, 5 , 103 , 157–161 in which Lactobacillus and bifidobacterium are the most commonly used, though the effects varied across studies, which depending on dosage, duration, and their components. 162 Several clinical trials have demonstrated that the intake of a probiotic mixture decreasing inflammatory levels, increased the abundance of an anti-inflammatory commensal bacterium and improved cognitive function in older people. 80 , 131 Additionally, studies have shown that some probiotic strains have beneficial effects on male reproductive dysfunction.…”
Section: Perspectivesmentioning
confidence: 99%
“…To help facilitate the discovery of novel microbiome-targeted interventions to delay the onset of cognitive decline and dementia, the Alzheimer’s Gut Microbiome Project [ 58 ] is investigating the influence of the MIND diet [ 59 ], a low carbohydrate ketogenic diet [ 60 ], and a healthy lifestyle intervention [ 61 ] on the gut microbiome, the metabolome, and cognitive function. These studies could pave the way for future research into microbiome-based interventions to help mitigate other geriatric syndromes [ 62 ]. In humans, changes in the intestinal microbiome can take months to years and a habitual or long-term diet is more likely to have a meaningful impact.…”
Section: Dietary Requirements and Intakes Of Older Adultsmentioning
confidence: 99%
“…Aging also affects the mucosal immune system, characterized by a decline in the production of goblet cells and a thinning of the mucus layer, weakening the adaptive immune response. 126,127 Dysbiosis associated with aging often reduces the abundance of Faecalibacterium prausnitzii, a butyrate-producing bacteria, contributing to increased gut inflammation. 126 Furthermore, the decline in proper immune function with age, known as immunosenescence, results in reduced antigen recognition by dendritic cells, decreased memory of T cells, and chronic low-grade inflammation.…”
Section: Reviewmentioning
confidence: 99%
“…126 Furthermore, the decline in proper immune function with age, known as immunosenescence, results in reduced antigen recognition by dendritic cells, decreased memory of T cells, and chronic low-grade inflammation. 127 These immune alterations are reflected in modification in microbiota composition, characterized by a decrease in Firmicutes abundance (ex. Lactobacillus) and Actinobacteria (ex.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation